Влияние морфологии порошков кубического нитрида бора на свойства спекаемых на их основе при высоких давлении и температуре поликристаллов и композитов - Лошак, М.Г.; Шульженко, А.А.; Александрова, Л.И.; Мельничук, Ю.А.; Муковоз, Ю.А.; Боримский, И.А.; Заика, Н.И.; Лысаковский, В.С. (Породоразрушающий и металлообрабатывающий инструмент – техника и технология его изготовления и применения, 2008)
Cubonit cBN powders produced in different growing systems were tested in free state und in the form of composites prepared from these powders by sintering at high pressures and temperatures. It is shown that in cutting metals the properties of the Composites may not correspond to those of starting powders in strength.